Spirituality and health in the society of the spectacle: DOI: 10.15343/0104-7809.200731.2.8 - da Mata Ribeiro Monteiro, Dulcinéa (2007)
Humans are the only animals that pose to themselves the ontological question of their origins and ends, searching for thesense of life - that is, spirituality. Spirituality is not necessarily linked to any religious belief, although they are different answers givenby men to the questions of human existence. Scholars that study current society describe it using different denominations, from whichone stands out: the Society of the Spectacle, impregnated by the values articulated to material life: body, sensations and hedonism,physical appearance and aesthetic of youth as a way to deny the passage of time and the basic reality of our condition of beings thatmarch to death; consumerism and expansion of wealth and material goods; a severing from subjective reality and submission to theexternal reality of having and seem to have. To sum up, produced by this focus of values, we perceive the superficiality of a life thatsearches to keep the appearances, separating us from the reality of the soul and the spirit. The present article intends to present reflectionsarticulating the spiritual emptiness of modern man and the possible implications regarding processes of physical and psychicdiseases. Like shipwreck survivals we are lost, with no compass to guide and support us before the reality of life in the alternation ofits opposites; we lack reference points that are in the framework of sense and meaning – i.e., spirituality. Because of all this, to reflecton the axis health-illness lead us towards the foundations of spirituality, with evidence from current research, and also give healthprofessionals guidelines for therapeutic relations.